2023
DOI: 10.1021/acsbiomaterials.3c00491
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Titanium Surfaces with Positive Charges: Newly Developed Cationic Coating Combines Anticorrosive and Bactericidal Properties for Implant Application

Abstract: Along with poor implant−bone integration, peri-implant diseases are the major causes of implant failure. Although such diseases are primarily triggered by biofilm accumulation, a complex inflammatory process in response to corrosive-related metallic ions/debris has also been recognized as a risk factor. In this regard, by boosting the titanium (Ti) surface with silane-based positive charges, cationic coatings have gained increasing attention due to their ability to kill pathogens and may be favorable for corro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…In addition to polymeric antibacterial coatings, various studies have reported on coatings based on lipids and those developed from nanoparticles [ 26 , 68 , 69 , 70 ]. Owing to their potential responsivity to external stimuli (including magnetic field, temperature, and light) and typical strong antibacterial effects, metallic nanoparticles are one of the most utilized nanomaterials for antibacterial coatings, either by direct immobilization or embedding in polymeric layers [ 71 , 72 ].…”
Section: Biofilm Formation On Orthopedic Implants and Prevention Stra...mentioning
confidence: 99%
“…In addition to polymeric antibacterial coatings, various studies have reported on coatings based on lipids and those developed from nanoparticles [ 26 , 68 , 69 , 70 ]. Owing to their potential responsivity to external stimuli (including magnetic field, temperature, and light) and typical strong antibacterial effects, metallic nanoparticles are one of the most utilized nanomaterials for antibacterial coatings, either by direct immobilization or embedding in polymeric layers [ 71 , 72 ].…”
Section: Biofilm Formation On Orthopedic Implants and Prevention Stra...mentioning
confidence: 99%